The Role of Social Media in Building Brand Image: The Influence of Storytelling Marketing and User-Generated Content on Hmns Perfume - Alfiaturrakhmania, Aisyah; Awalil Fakhri, Erie (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this research is to identify the effects of storytelling marketing and user-generated content on the brand image of HMNS, a local perfume brand dominating Indonesian market, among the Instagram account followers of @hmns.id. From 140 population members, 120 people meeting the sample criteria were involved as respondents. The data of this quantitative study was harvested via online questionnaires, analyzed using SEM-PLS. The results demonstrate that storytelling marketing and user-generated content positively and significantly influence the image of the brand and that the former variable is more dominant in affecting the brand image than the latter. Further, storytelling marketing enables HMNS to create appealing narratives and create emotional bonds with the consumers, creating functional, symbolic, and experiential brand image. User-generated content helps the establishment and elucidation of the brand’s image, becoming a credible information source directly produced and shared by its consumers. Additionally, such content digitally strengthens the community of HMNS perfume consumers. Therefore, both strategies are effective to be applied in perfumery and similar industries in the field of digital marketing via social media.